Investigation the Application State of ISO9001:2000 for QualityManagement Systemof Al-Rasheed State Contracting ConstructionCompany - Hatim Mahmoud, Awss (Iraqi Journal of Civil Engineering, 2008)
ABSTRACTConstruction industry is becoming an increasingly global business. Competition in theindustry is intensifying, and projects are becoming larger and more complex. Customersare becoming more demanding, and increasingly they are looking for complete packagesof construction services. In this environment, the relationships between suppliers, projectmanagers and customers are the key to success. Customers will need to be confident thatcompanies can get the job done. Companies will need to develop plans, communicate andeffectively fulfill these plans, in order to successfully complete projects.Building quality management system (QMS) based on ISO 9001:2000, require managingcompany as a system of interrelated processes, management should plan these processes,identify how they relate to each other, set goals, measure processes and makeimprovements.The objective of this research is to review the concept, definition, principles, and benefitsof ISO 9001:2000 standard and developing the application of the quality managementsystem for Al-Rasheed State Contracting Construction Company.KEYWORDS: ISO 9001:2000 standard, quality, quality management system, customersatisfaction, continuous improvement